The effectiveness of guidance and counseling services implementation to improve students’ competency standards - Sihite, Julius Martunas (Journal of Advanced Guidance and Counseling, 2023)
Purpose - This article aims to determine the effectiveness of the implementation of guidance and counseling services to improve students' affective competency standards.Method - This article uses a literature review method or approach. At the same time, data collection is done by reviewing and studying several journals, books, and documents (both printed and electronic), as well as raw data and information related to the study.Result - The results of the study are 1) guidance services can be carried out through various forms of pre/post-learning games, and 2) student diaries (recording and assessing students' daily activities) are carried out as in-class guidance. Independence development strategy; 3) Effective guidance and counseling services in improving students' competency standards can be seen in filling out the Student’s Daily Journal; 4) Professional consultants must still carry out consultation.Implication - The key to the success of a counseling service is the teacher's ability to build interactive dialogue while reviewing and evaluating daily journals (students’ activity records).Originality - This paper is one of the developments in counseling science in terms of identifying problems that hinder student development in achieving educational goals.***Tujuan - Artikel ini bertujuan untuk mengetahui efektivitas pelaksanaan layanan bimbingan dan konseling untuk meningkatkan standar kompetensi afektif siswa.Metode - Artikel ini menggunakan metode atau pendekatan tinjauan literatur. Sedangkan pengumpulan data dilakukan dengan mengkaji dan mempelajari beberapa jurnal, buku, dan dokumen (baik cetak maupun elektronik), serta data dan informasi mentah yang terkait dengan penelitian.Hasil - Hasil dari penelitian tersebut adalah 1) layanan bimbingan dapat dilakukan melalui berbagai bentuk permainan pra/pasca pembelajaran, dan 2) buku harian siswa (pencatatan dan penilaian kegiatan harian siswa) dilakukan sebagai bimbingan dalam kelas. Strategi pengembangan kemandirian; 3) Layanan bimbingan dan konseling yang efektif dalam meningkatkan standar kompetensi siswa dapat dilihat pada pengisian Jurnal Harian Siswa; 4) Konsultan profesional harus tetap melaksanakan konsultasi.Implikasi - Kunci keberhasilan layanan BK adalah kemampuan guru dalam membangun dialog interaktif saat mereview dan mengevaluasi jurnal harian (catatan kegiatan siswa).Keaslian - Makalah ini merupakan salah satu pengembangan ilmu konseling dalam hal mengidentifikasi masalah yang menghambat perkembangan siswa dalam mencapai tujuan pendidikan.